2018
DOI: 10.1002/chem.201800607
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐Containing Radical Anions via Single Electron Transfer to Donor–Acceptor Adducts

Abstract: Reactions of [Cp* Fe] with the Lewis acid [Zn(C F ) ] in the presence of [(PhC(S)S) ], 9,10-phenanthrenedione or 4,5-pyrenedione yield the salt [Cp* Fe][(PhC(S)S)Zn(C F ) ] 1, [Cp* Fe][((C H O )Zn(C F ) )⋅] 4, and [Cp* Fe][((C H O )Zn(C F ) )⋅] 5, respectively. The latter two species represent the first examples of isolable zinc-containing radical anions. While [(PhC(S)S) ] binds weakly to [Zn(C F ) ], the diones afford the isolable adducts [(C H O )Zn(C F ) ] 2 and [(C H O )Zn(C F ) ] 3. Cyclic voltammetry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…It appears that PQ-Δ is reduced fully to the dianionic state in each PQ unit (PQ-Δ 6− ) and interacts with three zinc dictations (PQ-Δ-Zn 3 ), an observation that has not been reported previously. 20 Recent investigations 25 have led to the reporting of the crystal structure of Zn(C 6 F 5 ) 2 , which displays a fully reversible redox process behavior, indicative of the favorable coordination of Zn 2+ dications with the dione functional groups. Additional galvanostatic cycling measurements, carried out at a current rate of 30 mA g −1 , confirmed that AQ-PQ-Δ features (Figure 2b and Figure S7a) extremely stable cycling behavior, preserving 100% of the initial capacity over 30 cycles without any loss.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that PQ-Δ is reduced fully to the dianionic state in each PQ unit (PQ-Δ 6− ) and interacts with three zinc dictations (PQ-Δ-Zn 3 ), an observation that has not been reported previously. 20 Recent investigations 25 have led to the reporting of the crystal structure of Zn(C 6 F 5 ) 2 , which displays a fully reversible redox process behavior, indicative of the favorable coordination of Zn 2+ dications with the dione functional groups. Additional galvanostatic cycling measurements, carried out at a current rate of 30 mA g −1 , confirmed that AQ-PQ-Δ features (Figure 2b and Figure S7a) extremely stable cycling behavior, preserving 100% of the initial capacity over 30 cycles without any loss.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A recent investigation has shown that phenanthrene­quinone ( PQ ) coordinates to bis­(pentafluorophenyl)­zinc Zn­(C 6 F 5 ) 2 and that the complex can undergo readily a reversible redox process. In addition, DFT calculations on this phenanthrene­dione-based organozinc complex have revealed that the lowest unoccupied molecular orbitals (LUMOs), which are primarily π*-antibonding orbitals associated with the dione, are significantly lower in energy than the free diones. In this context, the redox process occurs on the dione moieties without any contribution to the redox process from the coordinated Zn 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reaction of B(C 6 F 5 ) 3 with 3d (2 : 1 molar ratio) in dichloromethane followed by the treatment of the resulting dark brown solution with (one molar equiv.) 21 gave the respective [(C 6 F 5 ) 3 B] 2 –9,10-phenanthrene–semiquinone radical anion, which was isolated as the salt 13c as a brown crystalline material in 81% yield after workup involving crystallization at –35 °C ( Scheme 6 ). Compound 13c was characterized by C, H elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…While such combinations alone show no reactions, in the presence of disulfides, ditelelurides or elemental S, Se and Te the reactions proceed via the elusive radical anions [E(C 6 F 5 ) 3 ] .− prompting homolytic cleavage of chalogenide‐chalcogenide bonds to give a series of unusual ferrocenium salts of chalcogenide‐boron/aluminum‐based anions . Analogous reactions using Zn(C 6 F 5 ) 2 as the Lewis acid were also reported . Erker et al subsequently reported the reactions of the transient radical [B(C 6 F 5 ) 3 ] .− with quinones while we showed the cleavage of peroxides with the FRP derived from Mes 3 P and B(C 6 F 5 ) 3 .…”
Section: Methodsmentioning
confidence: 99%